Fruits of Rosa laevigata and its bio-active principal sitostenone facilitate glucose uptake and insulin sensitivity in hepatic cells via AMPK/PPAR-γ activation - K.J. Senthil Kumar; Chun Lin; Yen-Hsueh Tseng; Sheng-Yang Wang (Elsevier, 2021)
Background: Fruits of Rosa laevigata Michx is commonly used in traditional Chinese medicine for treating of spleen deficiency, chronic diarrhea, and chronic urinary tract infection. Recently, fruits of R. laevigate have been shown to have renal protective effects in diabetic rats. However, up to now, no studies have been reported on the anti-hyperglycemic or anti-diabetic effect of R. laevigata or its derived compounds. Purpose: Therefore, this study investigated the anti-diabetic effect of ethanol extract of R. laevigata (EtRL) fruits, its derivate sub-fractions, and pure compounds in terms of glucose-lowering effect on hyperglycemia-induced hepatic cells in vitro. Methods: We investigated the anti-hyperglycemic effect of EtRL and its derivate sub-fractions (water, n-butanol, ethyl acetate, and n-hexane), and its major bioactive compound, sitostenone, in normal and high glucose-induced insulin-resistant hepatic HepG2 cells using in vitro DNS glucose uptake and Western blotting assays. Results: Treatment with EtRL and its derivate sub-fractions significantly increased glucose uptake by hepatic cells. Besides, co-treatment with insulin further improved glucose uptake in insulin-resistant cells. Notably, compared with all soluble fractions, the n-hexane sub-fraction displayed the strongest activity in the context of glucose consumption. Furthermore, sitostenone, a primary bioactive compound was isolated from n-hexane sub-fraction by bioactivity-guided fractionation procedure. Sitostenone treatment significantly increased glucose uptake, whereas there was no further increase when co-treatment with insulin. Indeed, sitostenone significantly increased glucose uptake and promote insulin sensitivity in insulin-resistant cells. Further analysis revealed that sitostenone activates proteins involved in the insulin signal transduction pathway, including insulin receptor substrate-1 (IRS-1), AKT, and glycogen synthase kinase 3 β (GSK3β). It was also found that sitostenone provoked glucose uptake in insulin-resistant cells via peroxisome proliferator-activated receptor-γ (PPAR-γ) and AMP-activated protein kinase (AMPK) activation, which facilitates up-regulation of glucose transporters, GLUT2 and GLUT4 in the cell membrane and down-regulation of Forkhead box protein O1 (FOXO1) in the nucleus. Conclusion: This study demonstrating that sitostenone, a steroid-like compound from fruits of R. laevigata has a promising ability to promote glucose uptake and repairs insulin resistance in hepatic cells.